Antimicrobial activity, antiproliferative activity, amylase inhibitory activity and phytochemical analysis of ethanol extract of corn (Zea mays L.) silk - S. Abirami; M. Priyalakshmi; A. Soundariya; Antony V. Samrot; S. Saigeetha; Renitta R. Emilin; S. Dhiva; L. Inbathamizh (Current Research in Green and Sustainable Chemistry, 2021)
In this study, ethanolic extract of Zea mays L was utilized against urinary tract infection (UTI) causing bacteria, vegetable spoilage causing fungi and anticancer activity. The antimicrobial activity of ethanol extracts of corn silk was determined by the agar well diffusion method against UTI pathogens. The most effective antibacterial activity of ethanol corn silk extract was found at 900 ​μg and antifungal activity was found against Aspergillus niger and Aspergillus brasiliensis at 2mg/20 ​ml. It showed 75% nitric oxide inhibition activity and 67%. amylase inhibiting activity. GC-MS analysis showed several bio active compounds with antimicrobial, antioxidant, anticancer activities etc.